Carotid artery dissection recanalization: imaging modalities, influencing factors, and therapeutic perspectives - Li, Tao; Lan, Wenjing; Zhang, Xuanxiao; Yin, Shuo; Sun, Pengfei; Chen, Xin; Zhou, Hongwei (Frontiers in Neurology, 2025)
Carotid artery dissection (CAD) is a rare cause of ischemic stroke, and its prognosis is often poor. If not diagnosed and treated in time, it may lead to serious complications such as intracranial stroke and even death. Accurate diagnosis of CAD, formulation of reasonable treatment plans, and prediction of vascular recanalization are crucial for improving the prognosis of patients. However, there is currently a lack of large-scale randomized controlled trials to provide guidance for clinical practice, and the industry has not yet reached a unified consensus on the standardized diagnosis and treatment of CAD. Therefore, this article reviews the imaging examination methods for recanalization of CAD, the analysis of related factors affecting recanalization, and the methods of recanalization treatment, and combines the latest research progress to provide a perspective on the recanalization of carotid artery dissection, aiming to provide a reference basis for the precise diagnosis and treatment of CAD recanalization.